2010
DOI: 10.1016/j.jcv.2010.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease due to human coronavirus NL63 infections and periodicity of infection

Abstract: HCoV-NL63 infection in children below 3 years of age often requires a visit to the physician in an outpatient clinic, especially during peak-years, but hospitalizations are relatively infrequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 27 publications
(29 reference statements)
4
43
0
2
Order By: Relevance
“…Different HCoV species predominated in different years; HCoV-OC43 appeared to peak annually, while HCoV-NL63, HCoV-HKU1, and HCoV-229E showed more variability, with distinct peaks in one or two of the three years studied. This is consistent with previously published site-specific data indicating that individual species may only demonstrate peak activity every 2-3 years [10,11].…”
Section: Discussionsupporting
confidence: 93%
“…Different HCoV species predominated in different years; HCoV-OC43 appeared to peak annually, while HCoV-NL63, HCoV-HKU1, and HCoV-229E showed more variability, with distinct peaks in one or two of the three years studied. This is consistent with previously published site-specific data indicating that individual species may only demonstrate peak activity every 2-3 years [10,11].…”
Section: Discussionsupporting
confidence: 93%
“…3,19,20 In the majority of the abovementioned studies only 1 year was sampled and for HCoVs a large year-to-year periodicity is known. 14,21,22 The significant differences of seroconversion rates between the coronaviruses observed here cannot be attributed to variable circulating frequencies as samples were collected over multiple years.…”
Section: Discussionmentioning
confidence: 84%
“…The periodicity of coronavirus infection is also described in other reports. 4,8 The majority of HCoV-HKU1 positive patients (78.9%, 15/19) were ≤5-years-of-age, which indicated that young children are at high risk of HCoV-HKU1 infection. HCoV-HKU1 was only detected from November to April in this study, with a peak in January and February, which agrees with USA, Hong Kong, and Italian reports.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Recently three novel human coronavirus were identified, including severe acute respiratory syndrome coronavirus (SARS-CoV), human coronavirus Netherlands (HCoV-NL63), and human coronavirus Hong Kong (HCoV-HKU1). [5][6][7][8] HCoV-HKU1 was first isolated in 2005 from a 71-year-old man with pneumonia. 6 Several successive reports confirmed retrospectively that HCoV-HKU1 was circulating worldwide.…”
Section: Introductionmentioning
confidence: 99%